INTRODUCING THE ENGLISH LANGUAGE IN PRIMARY SCHOOL = FADING AWAY AN ETHNIC LANGUAGE AMONG FUTURE YOUNG GENERATION - SUSENO, EDY (Innovare Journal of Social Sciences, 2021)
The Indonesian government puts an English lesson at the primary school. On the other hand, it has an intention to preserve local languages. The presence of the two additional lessons in the same school invites a certain problem. Through the questionnaire distributed randomly to 26 primary school parents whose children learn English and Javanese at school in 4 different cities like Surabaya, Sidoarjo, Gresik, and Malang, it could be found out that many students got the competencies of lowering the usage of local language at home, switching codes, lowering competence in implementing Javanese script and constructing sentences, unwilling to watch Javanese news, lowering local culture appreciation, and lowering the usage of local language among peers. Furthermore, in the comparative in English and Javanese learning the students had a lower interest in competing for language, appreciating culture, and literacy in Javanese.